The role of wetlands in the landscape and their utilisation in wastewater treatment - Németh, Nóra (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
Due to their unique ecological role played in the environment, both natural and constructed wetlands are getting into the focus of attention and research projects.During the past decades, several useful characteristics of wetlands have been recognised. They play an important role in water storage and in the regulation of erosion and runoffs, provide mining possibilities, biomass produced here can be used in different ways, at the same time they have outstanding function from the point of view of wild animals and plants, conservation of the gene pool and biodiversity, they take part in the material and energy cycle, and they have a role in education and training and recreation as well.Wetlands are the most valuable areas of our environment, but at the same time they are also the most endangered ones. They reflect to the natural characteristics and conditions of the environment, therefore their conservation and protection have got outstanding importance from the ecological, social and environmental point of view. Among them, reed communities are able to transform and eliminate pollutants, adsorb, adsorb and accumulate elements and nutrients, thus they are often considered to be the „kidney of the country”. These features are applied in the treatment of polluted waters.During the research period, author examined the wastewater, the soil and the plant (Phragmites australis (Cav.) Trin. ex Steudel) together in a root zone system used to treat municipal wastewater, which issue is not very well discussed in the former publications. Researchers examine these systems mainly from the point of view of water quality parameters, though, the role of the three factors mentioned above are strongly related to each other. The understanding of the role of the plant in element accumulation was emphasised, which enables us to understand the operation of the system and lay down the ecological bases of planning. A picture is given how plants live in an environment where the nutrient and element concentrations are higher than in their natural habitat.Natural-like systems cannot be neglected from the environmental point of view, and a monitoring system is needed to help the operation of the system based on experience and observations.
Keywords: wetland; wastewater treatment; sustainability; environmentally friendly; systems fitting in the landscape